2022
DOI: 10.3389/fsufs.2022.936157
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Effects of COVID-19 Pandemic on Food Security in Southeast Nigeria

Abstract: The present study evaluated the perceived effects of the COVID-19 Pandemic on food security in Southeast Nigeria. A multi-stage random technique was used to select 209 households. Data for the study were collected with the aid of a structured questionnaire and were analyzed using descriptive statistics, z-test, food security model, and Tobit regression model. Results showed that the mean household size was 9.6 persons, which indicates a large household size. The percentage rate of food consumption of the house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…Studies that employed the use of a minimum recommended daily calorie requirement per adult equivalent were not consistent with the use of a unified recommended calorie required per adult equivalent. The minimum recommended calories of the thirteen studies ranged from 1800 Kcal [119] to 2700 Kcal [49]. There is a need for a single minimum recommended calorie to be used in determining FI among different settings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies that employed the use of a minimum recommended daily calorie requirement per adult equivalent were not consistent with the use of a unified recommended calorie required per adult equivalent. The minimum recommended calories of the thirteen studies ranged from 1800 Kcal [119] to 2700 Kcal [49]. There is a need for a single minimum recommended calorie to be used in determining FI among different settings.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies used different daily calorie requirements; for instance, both [88] and [62] used 2250 Kcal, while [71] used 2500 Kcal; [75] used 2550 Kcal; [68] used 2470 Kcal; and [49] utilized the highest value of 2710 Kcal. Also, [126] utilized a 2145 Kcal per capita calorie intake, while [119] used three minimum recommended calorie benchmarks of 2100 Kcal, 1800 Kcal, and 2700 Kcal in their study, which focused on the perceived effects of COVID-19 on food security in southeastern Nigeria. Furthermore, an approach through the per capita food expenditure of households was used in ten studies.…”
Section: Quantifying Food Insecuritymentioning
confidence: 99%
See 1 more Smart Citation
“…To afford nutritious food is a global challenge to many households today. According to the Food and Agriculture Organization (FAO), the outbreak of Covid-19 was harmful in 2 prominent ways namely: food supply-and food-demand, and were directly related to food insecurity (FAO, 2020).The presence of Coronavirus disease has a negative impact on all the four pillars of food security which included but not limited to: availability of food, accessibility of food, utilization of food, and stability of food (Nechifor et al, 2021;Laborde et al, 2020;Munonye et al, 2022). According to Genkin and Mikheev (2020), the report by the (FAO), World Trade Organization, and World Health Organization (WHO) noted the threat of a food catastrophe triggered by the current Corona-virus pandemic, with a risk of a global "food shortage".…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has also had indirect effects on food security. For instance, a study conducted in Brazil found that social distancing measures and lockdowns imposed during the pandemic were determinants of household food security status (Munonye et al, 2022). Additionally, the pandemic has exacerbated economic hardship, food insecurity, and psychological distress among vulnerable populations, as observed in studies conducted in low-income countries (Porter et al, 2021) and among Supplemental Nutrition Assistance Program (SNAP) and food pantry clients in the United States (Higashi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%